Rho-omega mixing and the Nolen-Schiffer anomaly in relativistic nuclear models - Barreiro, L. A. [UNESP]; Galeão, A. P. [UNESP]; Krein, G. [UNESP] (Elsevier B.V., 1995)
We calculate within the framework of relativistic nuclear models the contribution of the ρ0 - ω mixing interaction to the binding energy differences of the mirror nuclei in the neighborhood of A = 16 and A = 40. We use two relativistic models for the nuclear structure, one with scalar and vector Woods-Saxon potentials, and the Walecka model. The ρ0 - ω interaction is treated in first order perturbation theory. When using the Walecka model the ρ- and ω-nucleon coupling constants are the same for calculating bound state wave functions and the perturbation due to the mixing. We find that the relativistic results on the average are of the same order as the ones obtained with nonrelativistic calculations.